2022
DOI: 10.1021/acs.jmedchem.2c01517
|View full text |Cite
|
Sign up to set email alerts
|

Design and Structural Optimization of Orally Bioavailable SOS1 Inhibitors for the Treatment of KRAS-Driven Carcinoma

Abstract: KRAS mutations (G12C, G12D, etc.) are implicated in the oncogenesis and progression of many refractory cancers. Son of sevenless homolog 1 (SOS1) is a key regulator of KRAS to modulate KRAS from inactive to active states. Herein, we disclosed efficacy-improving tetra-cyclic quinazoline derivatives as an enhanced scaffold for inhibiting the SOS1–KRAS interaction. Compound 37, which conjugated 1-carbonitrile-cyclopropane to tetra-cyclic quinazoline, showed a twofold higher oral drug exposure and 2.5-fold longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…Another compound, MRTX0902 , with a pyridopyridazine core, has just entered clinical trials (NCT05578092), which are designed to elucidate the effectiveness of MRTX0902 , either alone or in combination with MRTX849 (adagrasib), in treating solid tumours malignancies among patients harbouring KRAS G12C mutations. 12 Similar research has been published by Revolution Medical 13 and He et al 14,15 for the SOS1 inhibitors: RMC-0331 with a pyrrolo [3,4- d ]pyrimidine scaffold and the tetracyclicquinazoline ( 37 and 13c ) with superior pharmacokinetic properties, respectively (see Fig. 2 ).…”
Section: Introductionsupporting
confidence: 64%
“…Another compound, MRTX0902 , with a pyridopyridazine core, has just entered clinical trials (NCT05578092), which are designed to elucidate the effectiveness of MRTX0902 , either alone or in combination with MRTX849 (adagrasib), in treating solid tumours malignancies among patients harbouring KRAS G12C mutations. 12 Similar research has been published by Revolution Medical 13 and He et al 14,15 for the SOS1 inhibitors: RMC-0331 with a pyrrolo [3,4- d ]pyrimidine scaffold and the tetracyclicquinazoline ( 37 and 13c ) with superior pharmacokinetic properties, respectively (see Fig. 2 ).…”
Section: Introductionsupporting
confidence: 64%
“…42 He et al reported the discovery of a tetracyclic quinazoline scaffold as the potent orally bioavailable SOS1 inhibitor (Figure 12). 95 With the assistance of molecular dynamics simulations, they carried out a cyclization strategy at the 6-and 7-position of BI-3406 to obtain a series of tricyclic and tetracyclic quinazolines. Although tricyclic compound 36 (SOS1 IC 50 = 122 nM measured by an HTRF method) possessed less ability in the SOS1 inhibition than BI-3406, tetracyclic compound 37 showed higher potency (SOS1 IC 50 = 4.3 nM) and significantly inhibited p-ERK in DLD-1 cells.…”
Section: Sos1 Inhibitorsmentioning
confidence: 99%